2020
DOI: 10.1371/journal.pone.0241578
|View full text |Cite|
|
Sign up to set email alerts
|

Is consumer neural response to visual merchandising types different depending on their fashion involvement?

Abstract: This study investigated consumers' responses to fashion visual merchandising (VM) from a neuroscientific perspective. The brain activations of 20 subjects differently involved in fashion were recorded using functional near-infrared spectroscopy in response to three different fashion VM types. According to the types of fashion VM, significant differences were observed, which were significantly higher for the creative VM. Moreover, highly fashion-involved subjects showed activation of the orbital frontal cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…A study showed a user-friendly website screen and a user-unfriendly website screen and then used a fNIRS to detect brain PFC activity 60 . Another study was discovered that visual commercialization enhanced consumers' impulse buying behavior, resulting in a change in brain activation 61 . Therefore, website designs influence impulse buying behavior by providing powerful visual stimulation, which has a significant influence on PFC activation, and brain activation for specific impulse buying behavior can be observed using an fNIRS.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed a user-friendly website screen and a user-unfriendly website screen and then used a fNIRS to detect brain PFC activity 60 . Another study was discovered that visual commercialization enhanced consumers' impulse buying behavior, resulting in a change in brain activation 61 . Therefore, website designs influence impulse buying behavior by providing powerful visual stimulation, which has a significant influence on PFC activation, and brain activation for specific impulse buying behavior can be observed using an fNIRS.…”
Section: Discussionmentioning
confidence: 99%
“…Also recommended that future researchers consider other demographic groups as only one could have marginalized the results. (Kim et al, 2020) In the complex modern society and under intensifying competition, a strategic fashion VM must be implemented to suit the purpose and situation for consumer critical burial operations. Since the results of this study show different brain responses to VM types depending on the level of fashion involvement, it will be useful for companies or brands to understand better the level of fashion involvement of consumers targeted and create a store with the appropriate VM type.…”
Section: Visual Merchandising and Fashion Trendsmentioning
confidence: 99%
“…Additionally, the underlying creative process must be responsive to the data, which is reflective of the current trends, popular demand, seasonality, operational limits, cost-effectiveness, etc. [9] There is a consumers' responses to fashion visual merchandising (VM) from a neuro-scientific perspective. The brain activation of the subjects showed significant differences according to the fashion VM types.…”
Section: Visual Merchandising and Apparel Fashion Trendsmentioning
confidence: 99%